CORRECTIONS OF MAXIMUM SPEED ACHIEVED BY FREIGHT TRAINS (Perner's Contacts, 2012)
Article deals with method of continuous corrections of maximum speed achieved by trains in Base simulation, part of traffic intelligence module for automatic train route setting.
Keywords: automatic train route setting, event-updated simulation